School outside the door: How (and why) to teach science outdoors - experiences of Czech primary school teachers - Vašutová, Dagmar; Vrbová , Irena (Scientia in educatione, 2025)
Outdoor education (OE) has often been included as a powerful teaching strategy in recent years during science education. Moreover, it is mentioned in current educational documents as a prerequisite for their implementation - in the form of linking formal education with non-formal education. However, few research surveys are mapping the actual form of OE in schools in the Czech Republic, which is why a questionnaire survey was conducted in 2023. 261 questionnaires were obtained from primary school teachers in several regions in the Czech Republic. The questions focused on the frequency and forms of OE, its limits and positives, and others. Most of the respondents (94%) answered that they realize OE. The most frequent form of OE was a short field trip (36%) and more than half of the respondents (60%) said they cooperate with other organizations. Despite the identified problems of OE (weather, lack of time, etc.), most announced (65 %) that OE needs to be strengthened and given much more time. The survey also tested two hypotheses concerning the influence of school location and cooperation with other organizations on the frequency of OE implementation. The first one was statistically confirmed, but the second one not.